Technology and Application of Microbial Fuel Cells - Wang, Chin-Tsan (IntechOpen, 2014)
Faced with the upcoming serious deficiency of energy, food and water, along with inevitable environmental pollution, much related research has been on the upsurge because Microbial Fuel Cells (MFCs) seem to be one of the solutions to these concerns in the future. The aim of this book is to describe and consider some concepts regarding MFC application designs for interested colleagues. Five topics regarding the technology of flow control, biocatalysts, biofilms, removal of chemical oxygen demand and biochemical fields are addressed in the book. Considering the low power density and short life span of MFCs, there has been a dramatic increase in funding and research that has led to a greater understanding of the fundamental science behind MFC study. This is driving significant improvements in both the reliability and efficiency of MFCs and hence their future use.